Igneous intrusions in the Faroe Shetland basin and their implications for hydrocarbon exploration; new insights from well and seismic data. (April 2018) - Mark, N.J.; Schofield, N.; Pugliese, S.; Watson, D.; Holford, S.; Muirhead, D.; Brown, R.; Healy, D.
Abstract: Igneous sills and dykes that intrude pervasively into prospective sedimentary basins are a common occurrence in volcanic margins, impacting the petroleum system and causing geological and technical drilling challenges during hydrocarbon exploration. The Faroe-Shetland Basin (FSB), NE Atlantic Margin, has been the focus of exploration for over 45 years, with many wells penetrating igneous intrusions. Utilising 29 FSB wells (with 251 intrusions) and 3D seismic data, this study presents new insights into the impacts that igneous intrusions have on hydrocarbon exploration. Examination of cores reveals additional igneous material in individual wells, compared to estimates using seismic or petrophysical data alone, leading to potential underestimation of the volume of the igneous component in a basin. Furthermore, analysis of petrophysical data shows that within the FSB there are silicic intrusions such as diorite and rhyolite, in addition to the commonly encountered mafic intrusions. These silicic intrusions are difficult to recognise in seismic and petrophysical data due to their low density and compressional velocity and have historically been misidentified on seismic reflection data as exploration targets. Drilling data acquired through intrusions provide valuable insight into the problems exploration wells can encounter, often unexpectedly, many of which can be detrimental to safe drilling practice and result in prolonged non-productive time. Highlights: Mafic intrusions have characteristic subsurface properties making them easily identifiable in the subsurface. Thin igneous intrusions may be missed in seismic and log data resulting in low estimations of volume of igneous material. Silicic igneous intrusions can image poorly in seismic data and be misidentified as exploration targets. Igneous intrusions causes drilling issues, including loss of drilling fluids and abnormal pore pressures.